KEPEMIMPINAN CAMAT TAMPAN DALAM MENGKOORDINASIKAN UPAYA PENYELENGGARAAN KETENTRAMAN DAN KETERTIBAN UMUM DI KECAMATAN TAMPAN TAHUN 2016-2017 - Arfi, Bestari; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
AbstractThe Camat as the highest leader in the Subdistrict has the duty and responsibility in his government to guarantee the basic needs of the community in the field of peace and public order in the community. In this case the coordination of the camat as a leader is very necessary in the effort to organize peace and public order in the community. this is very clear because it has been regulated in the Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government, and also has been regulated in Government Regulation of the Republic of Indonesia Number 19 of 2008 concerning Subdistricts, wherein the regulation has regulated the duties and responsibilities of the camat in coordinating efforts to administer peace and public order at the District level.Tampan District has a very high public order rate compared to Other Districts in Pekanbaru City. Of course the leadership and coordination from the district head is needed in this regard. Therefore the formulation of the problem in this study is how the subdistrict leadership in coordinating the implementation of peace and public order in the District of Tampan and what are the factors causing sub-optimal leadership of the camat in this case, namely in 2016-2017. And the purpose of this study is to find out how the leadership of the subdistrict in coordinating efforts to organize peace and public order in the District of Tampan.The results of this study are that the leadership of the sub-district head as the highest leader in the District has been running well and properly. even the coordination between the camat and related parties such as the Police, Religious Leaders, Kelurahan, and related RTs and Rws has been proceeding as required. As well as the factors that have been used to strengthen coordination, the Camat has also done to overcome the problem of peace and order in Tampan District. The factors that influence the sub-optimal leadership of the camat in the implementation of peace and public order in the handsome district is not a priority to improve the disturbance of peace in the annual work plan of the District of Tampan where matters relating to peace and public order are not discussed in the District work plan. Next is the lack of participation of the community in running the siskamling in their environment so that many poskamling that do not operate even with the direction of the sub-district head's own post are difficult to walk because of the lack of community participation in this matter, so coordination in this case is difficult because community participation is needed in this regard.Â Keywords : Leadership, Coordination, Camat, Convenience, Regularity